Mutations of human TMHS cause recessively inherited non-syndromic hearing loss. Issue 8 (3rd February 2006) - Shabbir, M I; Ahmed, Z M; Khan, S Y; Riazuddin, Saima; Waryah, A M; Khan, S N; Camps, R D; Ghosh, M; Kabra, M; Belyantseva, I A; Friedman, T B; Riazuddin, Sheikh
Abstract : Background: Approximately half the cases of prelingual hearing loss are caused by genetic factors. Identification of genes causing deafness is a crucial first step in understanding the normal function of these genes in the auditory system. Recently, a mutant allele of Tmhs was reported to be associated with deafness and circling behaviour in the hurry-scurry mouse. Tmhs encodes a predicted tetraspan protein of unknown function, which is expressed in inner ear hair cells. The human homologue of Tmhs is located on chromosome 6p. Objective: To determine the cause of deafness in four consanguineous families segregating recessive deafness linked to markers on chromosome 6p21.1-p22.3 defining a novel DFNB locus. Results: A novel locus for non-syndromic deafness DFNB67 was mapped in an interval of approximately 28.51 cM on human chromosome 6p21.1-p22.3. DNA sequence analysis of TMHS revealed a homozygous frameshift mutation (246delC) and a missense mutation (Y127C) in affected individuals of two families segregating non-syndromic deafness, one of which showed significant evidence of linkage to markers in the DFNB67 interval. The localisation of mTMHS in developing mouse inner ear hair cells was refined and found to be expressed briefly from E16.5 to P3. Conclusions: These findings establish the importance of TMHS for normal sound transduction in humans.